2023
DOI: 10.30880/ijie.2023.15.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electrochemical Analysis of SmBa0.8Sr0.2Co2O5+δ Cathode Oxide for IT-SOFCs

Adi Subardi,
Ade Indra,
Jan Setiawan
et al.

Abstract: The double perovskite SmBa0.8Sr0.2Co2O5+δ(SBSC82)wasprepared using a conventional techniqueand evaluatedas solid oxide fuel cells (SOFCs) cathode materialwhich operatesat intermediate temperatures. The SBSC82 cathode powder was produced using the solid-state reaction technique and an alumina ball as a grinder. XRD was used to determine the cathode powder structure, and the microstructure was analyzed using SEM.The oxygen content (δ) for the SBSC82 cathode was recorded by a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Kim et al [86] observed improved chemical stability when GDC and LSGM electrolytes are used. Numerous investigations have systematically examined the electrical and electrochemical properties of the LnBa 1−x Sr x Co 2 O 5+δ system, with Ln representing La 3+ [73], Pr 3+ [87,92], Nd 3+ [90,91], Sm 3+ [87][88][89]112,114], and Gd 3+ [85][86][87]111]. Kim et al [86] demonstrated that the electrical conductivity of GdBa 1−x Sr x Co 2 O 5+δ increases with rising Sr content, attributed to increased oxygen content, which is believed to be linked to the difference in A-site cation radii between (Ba 1−x Sr x ) 2+ and Gd 3+ .…”
Section: Compositional Optimization Of Lnbaco 2 O 5+δmentioning
confidence: 99%
“…Kim et al [86] observed improved chemical stability when GDC and LSGM electrolytes are used. Numerous investigations have systematically examined the electrical and electrochemical properties of the LnBa 1−x Sr x Co 2 O 5+δ system, with Ln representing La 3+ [73], Pr 3+ [87,92], Nd 3+ [90,91], Sm 3+ [87][88][89]112,114], and Gd 3+ [85][86][87]111]. Kim et al [86] demonstrated that the electrical conductivity of GdBa 1−x Sr x Co 2 O 5+δ increases with rising Sr content, attributed to increased oxygen content, which is believed to be linked to the difference in A-site cation radii between (Ba 1−x Sr x ) 2+ and Gd 3+ .…”
Section: Compositional Optimization Of Lnbaco 2 O 5+δmentioning
confidence: 99%